When time is of the essence: Development and validation of brief consideration of future (and immediate) consequences scales. (February 2022) - Chng, Samuel; Chew, Han Shi Jocelyn; Joireman, Jeff
Abstract: Temporal dilemmas pose a conflict between the immediate and delayed consequences of one's actions. One trait related to decision-making in temporal dilemmas is the consideration of future consequences (CFC). Strathman et al. (1994) originally developed a (unidimensional) 12-item CFC scale (CFC-12), with five (seven) items tapping future (immediate) consequences. More recently, Joireman et al. (2012) created a balanced set of items (7 future, 7 immediate items), and argued that the CFC-14 scale contains CFC-Future and CFC-Immediate subscales. While the CFC-12 and CFC-14 scales have seen widespread application, they may be too long for certain research settings. Accordingly, the present work develops and validates brief 6-item (CFC-6) and very brief 4-item (CFC-4) scales. Drawing on ten CFC-14 samples ( N = 4789), evidence supports a two-factor structure and establishes the internal reliability and predictive validity of the brief (3-item) and very brief (2-item) subscales in comparison to the full-length scales: CFC-Future (3-item = 0.77, 2-item = 0.80) and CFC-Immediate (3-item = 0.83, 2-item = 0.83). Highlights: Developed two brief and reliable CFC scales, the CFC-6 and CFC-4 scales Both brief scales comprised of CFC-Future and CFC-Immediate subscales Findings for all scales support a two-factor structure of CFC Both brief scales predicted outcomes across multiple domains as well as the CFC-14